Review of cardiovascular involvements in COVID-19 - Ekpe EE; Umoh IA; Shogade TT; Eyo CS; Akpan AF (Ibom Medical Journal, 2021)
Background: A spectrum of cardiovascular pathologies occurs in patients with COVID-19 and increases the risk of mortality. Risk of mortality is also heightened in cardiovascular disease patients who contact COVID-19. Methodology: Online search for the keywords in PubMed, Medline, Embase, Google scholar was done. Relevant research articles yielded from the searches were reviewed. Results: the searches yielded a total of 172 results, out of which 111 were reviewed. Cardiac involvement was found in 70.6% COVID-19 patients: tachycardia (19%), electrocardiography abnormalities (22%), echocardiography abnormalities (57%), elevated myocardial enzymes (53%), and acute cardiac injury (9%). Eight percent of patients with acute cardiac injury were aged >60 years; 87.5% of them had ≥2 underlying comorbidities (hypertension, diabetes mellitus, cardiovascular diseases, chronic obstructive pulmonary disease, and chronic kidney disease). Novel coronavirus pneumonia was much more severe in the patients with acute cardiac injury than in patients with non-definite acute cardiac injury (P<0.001). Multivariate analyses showed that C-reactive protein (CRP) levels, old age, novel coronavirus pneumonia severity, and underlying comorbidities were the risk factors for cardiac abnormalities in patients with COVID-19. Conclusion: Besides its prominent expression at the level of the respiratory apparatus, COVID-19 is also characterized by a substantial degree of cardiovascular involvement, both in terms of deterioration of pre-existing conditions, and as the effect of inflammation-facilitated acute events. They include ischemic and inflammatory heart disease, ventricular arrhythmias, conduction disturbances, thrombotic events at the level of the lungs, systemic activation of the coagulation cascade and disseminated intravascular coagulation.